Dispositivo à fibra óptica baseados em interferência multimodal (MMI) para telecomunicações e sensoriamento - Balod, Yanes Checcacci (2011)
This paper describes and analyzes multimodal interference devices (MMI) for applications in telecommunications and sensing systems. This kind of sensor is less frequency studied in the literature compared with other types of optical sensors and at present has gained more attention. The sensing mechanism is proposed based on MMI phenomena created by the merger of a SI-SM to a GI-MM fiber. The system is potentially capable of monitoring the physical integrity of optical cables due to the high sensitivity in real time, untouched by the use of the traditional OTDR technique. The system is analyzed both qualitatively and quantitatively, dedicated to the phenomena that generate sensitivity and the best ways to improve it. In the first part of the work is described qualitatively and quantitatively as a first MMI reflective profile SMS modalmetric device , which are original contributions describing the device itself and demonstration of the statistical point of view of obtaining increased sensitivity with an increase in offset e SM/MM up to 6.8μm. There is a proposal of a technique for detecting and locating a disturbance through a simple algorithm via computer simulation in the active segment of the system (sensory fibers). In the second part of the work are analyzed 2x2 couplers formed by the fusion of optical fibers SI-SM and GI-MM. The device is classified as type MMI. Depends on the injection of light and door entry/exit used, behaving as one of three different types of optical filters or multimode interferometer (MMI). Upon completion of this work are suggested other lines of development applications for continuity of work and research.